Loss to follow-up in a cohort of HIV-negative men who have sex with men: Project Horizonte - Ana Paula Silva; Marília Greco; Maria Arlene Fausto; Mariângela Carneiro
ABSTRACT OBJECTIVE The objective of this study is to estimate the attrition rates and evaluate factors associated with loss to follow-up between 1994 and 2011 in an open cohort of HIV-negative men who have sex with men. METHODS The Project Horizonte is an open cohort study that aimed to assess the incidence of HIV infection, evaluate the impact of educational interventions, and identify potential volunteers for HIV vaccine trials. The rates of losses to follow-up were estimated for three periods (1994-1999, 2000-2005, and 2006-2011). The variables analyzed were collected in a psychosocial questionnaire. Volunteers who dropped out were compared with the ones who remained in the study using a Cox regression model. RESULTS A total of 1,197 volunteers were recruited. The median follow-up time in the study (n = 626) was 4.2 years. The median follow-up time for the volunteers who dropped out of the study (n = 571) was 1.46 years. The overall rate of loss to follow-up was 11.6/100 person-years. Attrition rates by period were: 12.60 (1994-1999), 11.80 (2000-2005), and 9.00 (2006-2011) per 100 person-years. Factors associated with losses to follow-up were: age group of 21-30 years old, monthly per capita income of more than six or less than one Brazilian minimum wage, having more than two dependents, report of bisexual practice, and inconsistent use of condoms for receptive anal sex. CONCLUSIONS A slight decrease of the loss to follow-up was observed over time. Higher attrition rates happened in the first three years of follow-up. It is possible that the link of the volunteers were not yet well established. Those who reported inconsistent condom use in receptive anal sex were more likely to leave the study, suggesting an underestimation of the incidence of HIV infection in a cohort population. For greater effectiveness, retention strategies must be reassessed considering the connection between the characteristics of homosexual and bisexual behavior and the motivations to engage in health research.